(untitled) (International Journal of Business, Economics and Management, 2024)
The purpose of the study was to investigate the impact of entrepreneurial orientation comprising autonomy, innovation, networking, and pro-activeness on business performance in Nepalese context. The literature of entrepreneurial orientation concerning to business performance depicted distinct directions with divergent and unsettled evidences. This research was conducted to address the research objective and for testing hypotheses. Thus, this study employed a descriptive and causal-comparative research approach, through cross-sectional data to gather information from participants to address research issues and objectives. A structured questionnaire of total 425 adopting the convenience sampling technique distributed among the targeted respondents in Kathmandu and received only 410 useful questionnaire for analysis. The findings of the study revealed that entrepreneurial orientation comprising autonomy, innovation, networking, and pro-activeness behavior found positively associated with the business performance of small and medium enterprises (SMEs) in Kathmandu, Nepal. There was a positive impact of entrepreneurial orientation on SMEs’ business performance. It showed that better entrepreneurial orientation leads towards better business performance. This research contributes for better understanding of the association between entrepreneurs’ orientation and business performance with their effect for business performance. This study establishes significant benchmark to a number of stakeholders consisting entrepreneurs, educators, academic institutions, regulators, and policymakers for a better understanding and optimum execution of the research outcomes to prepare effective policies for entrepreneurship development.